Usability and Feasibility of PreventS-MD Webapp for Stroke Prevention - Feigin, VL; Krishnamurthi, Rita; Medvedev, Oleg; Merkin, Alexander; Nair, Bala; Kravchenko, Michael; Jalili Moghaddam, Shabnam; Barker-Collo, Suzanne Lyn; Rathnasabapathy, Yogini; Skinner, Luke; Owolabi, Mayowa; Norrving, Bo; et al. (SAGE Publications, 2023)
Background: Most strokes and cardiovascular diseases (CVDs) are potentially preventable if their risk factors are identified and well controlled. Digital platforms, such as the PreventS-MD webapp (PreventS-MD) may aid health care professionals (HCPs) in assessing and managing risk factors and promoting lifestyle changes for their patients. Methods: This is a mixed methods cross-sectional 2-phase survey using a largely positivist (quantitative and qualitative) framework. During phase 1, a prototype of PreventS-MD was tested internationally by 59 of 69 consenting HCPs of different backgrounds, age, sex, working experience and specialities using hypothetical data. Collected comments/suggestions from the study HCPs in phase 1 were reviewed and implemented. In phase 2, a near-final version of PreventS-MD was developed and tested by 58 of 72 consenting HCPs using both hypothetical and real patient (n=10) data. Qualitative semi-structured interviews with real patients (n=10) were conducted, and 1-month adherence to the preventative recommendations was assessed by self-reporting. The four System Usability Scale (SUS) groups of scores (0-50 unacceptable; 51-68 poor, 68-80.3 good; >80.3 excellent) were used to determine usability of PreventS-MD. Findings: 99 HCPs from 27 countries (45% from low- to middle-income countries) participated in the study, out of whom 10 HCPs were involved in the development of PreventS before the study, and therefore were not involved in the survey. Of the remaining 89 HCPs 69 consented to the first phase of the survey, out of whom 59 completed the first phase of the survey (response rate 86%) and 58 HCPs completed the second phase of the survey (response rate 84%). The SUS scores supported good usability of the prototype (mean score=80.2; 95% CI [77.0-84.0]) and excellent usability of the final version of PreventS-MD (mean score=81.7; 95%CI [79.1-84.3]) in the field. Scores were not affected by the age, sex, working experience or speciality of the HCPs. One month follow-up of the patients confirmed the high level of satisfaction/acceptability of PreventS-MD and (100%) adherence to the recommendations. Interpretation: The PreventS-MD webapp has a high level of usability, feasibility and satisfaction by HCPs and individuals at risk of stroke/CVD. Individuals at risk of stroke/CVD demonstrated a high level of confidence and motivation in following and adhering to preventative recommendations generated by PreventS-MD.
Keywords: 1103 Clinical Sciences; 1109 Neurosciences; Neurology & Neurosurgery; 3202 Clinical sciences; 3209 Neurosciences; 4201 Allied health and rehabilitation science